Implementation of Green Product in Purchasing to Increase Environmental Awareness at Aston Canggu Beach Resort - Nugraha, Dicky Dwi; Sagitarini, Luh Linna; Sari, I Gusti Agung Mas Krisna Komala (Institut Pariwisata dan Bisnis Internasional, 2022)
The purchasing department is often said to be the buying center at the hotel company concerned. The purchasing department has a duty to ensure that the goods used for hotel operations do not damage the surrounding environment, currently environmental issues are important in economic development. The purpose of this study is to analyses the implementation of green products in purchasing at Aston Canggu Beach Resort and to analyse the relationship between the implementation of green products in an effort to increase environmental awareness at Aston Canggu Beach Resort. Methods of collecting data were observation, focus group discussions, questionnaires, documentation, and literature study. The data analysis method used is qualitative and quantitative methods, qualitative methods include several stages, namely data reduction, data presentation, and drawing conclusions, while quantitative research uses descriptive statistics. Indicators green product, including products that do not contain harmful elements when consumed, are made from environmentally friendly raw materials that provide recycling functionality, and products with production process technology used are environmentally friendly. While 1 indicator that has not been implemented is having efficiency in energy use, with the application of green products at Aston Canggu Beach Resort. It can increase environmental awareness as evidenced by the decrease in waste costs incurred by Aston Canggu Beach Resort.